Pengaruh Persepsi Korupsi Pajak,Kualitas Pelayanan Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak - Selpi Ayu Lestari; Karona Cahya Susena; Tito Irwanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine whether there is an influence of perceptions of tax corruption, service quality, and knowledge of taxation on the tax compliance of individual taxpayers registered at the Bengkulu Tax Service Office. The number of samples used in this study were 100 respondents. The research method used is quantitative.data collection used a questionnaire and the method of analysis used was multiple linear regression, determination test and hypothesis testing. The results of this study indicate that perceptions of tax corruption have no effect on individual taxpayer compliance. Meanwhile, service quality and knowledge of taxation have a significant positive effect on individual taxpayer compliance.The results of the multi linear regression equation Y = 0,089 + 0,082 X1 + 0,204 X2 + 0,710 X3 + 0,980 e, from the regression equation above can be explained as follows, a constans of 0,089 indicates that if the independent variabels (perceptions of tax corruption, service quality, and knowledge taxation) is assumed not to change (constans) then the value of Y (personal taxpayer compliance) is 0,089 units. The coefficient on the variable perception of tax corruption (X1) is 0,082, meaning that for every increase in the variable perception of tax corruption by 1 unit. The coefficient of the service quality variable (X2) is 0,204, meaning that for every increase oin the service quality variable, it is 1 unit. The coefficient on the variable knowledge of taxation (X3) is 0,710, meaning that for every increase in the variable knowledge of taxation by 1 unit.